A novel risk variant block across introns 36-45 of CACNA1C for schizophrenia: a cohort-wise replication and cerebral region-wide validation study - Guo, Xiaoyun; Wang, Shibin; Lin, Xiandong; Wang, Zuxing; Dou, Yikai; Cao, Yuping; Zhang, Yong; Luo, Xinqun; Kang, Longli; Yu, Ting; Wang, Zhiren; Tan, Yunlong; et al. (Psychiatric genetics, 2023)
Numerous genome-wide association studies have identified CACNA1C as one of the top risk genes for schizophrenia. As a necessary post-genome-wide association study (GWAS) follow-up, here, we focused on this risk gene, carefully investigated its novel risk variants for schizophrenia, and explored their potential functions. We analyzed four independent samples (including three European and one African-American) comprising 5648 cases and 6936 healthy subjects to identify replicable single nucleotide polymorphism-schizophrenia associations. The potential regulatory effects of schizophrenia-risk alleles on CACNA1C mRNA expression in 16 brain regions (n = 348), gray matter volumes (GMVs) of five subcortical structures (n = 34 431), and surface areas and thickness of 34 cortical regions (n = 36 936) were also examined. A novel 17-variant block across introns 36-45 of CACNA1C was significantly associated with schizophrenia in the same effect direction across at least two independent samples (1.8 × 10-4 ≤ P ≤ 0.049). Most risk variants within this block showed significant associations with CACNA1C mRNA expression (1.6 × 10-3 ≤ P ≤ 0.050), GMVs of subcortical structures (0.016 ≤ P ≤ 0.048), cortical surface areas (0.010 ≤ P ≤ 0.050), and thickness (0.004 ≤ P ≤ 0.050) in multiple brain regions. We have identified a novel and functional risk variant block at CACNA1C for schizophrenia, providing further evidence for the important role of this gene in the pathogenesis of schizophrenia.